2003
DOI: 10.1093/jac/dkg083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and types of class 1 integrons in aminoglycoside-resistant Enterobacteriaceae from several Chilean hospitals

Abstract: Members of the family Enterobacteriaceae are responsible for a variety of nosocomial infections, treatment of which is limited due to their increasing resistance to antibiotics. Some bacterial genes encoding antibiotic resistance comprise the major part of gene cassettes, most of which are associated with integrons. In this work, the carriage of class 1, 2 and 3 integrons was investigated in 191 Enterobacteriaceae isolates from clinical specimens of hospitalized patients. Class 1 integrons were found to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
3
12
1
10
Order By: Relevance
“…This highlights the increasing sophistication in the armory of these pathogens. The prevalence of integrons is relatively high as compared with some earlier reports, 10,11 yet is comparable with a report from the United States. 13 This high level of occurrence of integrons (62.6%) highlights the threat of MDR.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This highlights the increasing sophistication in the armory of these pathogens. The prevalence of integrons is relatively high as compared with some earlier reports, 10,11 yet is comparable with a report from the United States. 13 This high level of occurrence of integrons (62.6%) highlights the threat of MDR.…”
Section: Discussionsupporting
confidence: 84%
“…The simultaneous occurrence of two types of integrons in one E. coli isolate was significant, because it is relatively rare in clinical E. coli isolates. [10][11][12] To our knowledge, it is the first time in the world that two types of integrons have been amplified simultaneously in wound-infecting E. coli. This highlights the increasing sophistication in the armory of these pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Integrons are a type of mobile genetic elements thought to be associated with antibiotic resistance, and class 1 integrons were found to be the most common type of integrons in Enterobacteriaceae (45). Therefore, the presence of class 1 integrons in the 85 CRKP strains was investigated.…”
Section: Capsular Types Of Crkpmentioning
confidence: 99%
“…Plasmid genotypes were examined by the detection of integrons, replicon typing, and IncI1 plasmid multilocus sequence typing (IncI1 pMLST) as previously described (14)(15)(16). The PCR assay showed that all the conjugants contained a plasmid with the IncI1 replicon ( Table 1).…”
mentioning
confidence: 99%